Computer modeling of the fractional-differential dynamics of some filtration-consolidation processes - Bogaenko, V.A.; Bulavatsky, V.М. (Reports of the National Academy of Sciences of Ukraine, 2018)
Within the framework of models based on the concept of Caputo—Fabrizio fractional derivative, the com puter simulation of the fractional-differential filtration-consolidation dynamics of saltsaturated groundwa ter massifs is performed. The technique to obtain numerical solutions of the corresponding boundaryvalue problems for systems of fractional differential equations of filtration and salt transfer is developed, the approach to the parallelization of the computational process is described, and the results of numerical experiments on modeling the dynamics of the considered process are presented.